Effectiveness of cadre empowerment toward the coverage of stimulation, detection and intervention of early development children - Puji Hastuti, Retno; Fitarina (Proceedings Series on Health & Medical Sciences, 2020)
Stunting cases in North Lampung continuously increase due to lack of visits by mothers to perform stimulation, detection, early intervention for toddler development (SDIDTK). This study aims to determine the effectiveness of cadre empowerment on SDIDTK completion among children under five. The intervention of SDIDTK training for 50 cadres. The study used a Quasi-experimental Pre and Post-Test Design without control. Univariate data analysis with proportion, average, and standard deviation. Bivariate analysis using the Wilcoxon-test and Pearson Chi-Square Test. The results showed that there was a significant difference in the average score of knowledge of the cadres before and after the empowerment of cadres (p-value = 0.000). There was a significant correlation between cadre empowerment and the measurement completion of height, head circumference, and measurement of development (p-value = 0.000), however, there is no significant relationship between cadre empowerment and the completion of body weight measurement (p-value = 0.317). Suggestions for Health workers and health offices to carry out training on SDIDTK to all cadres, to provide guidance and motivation, and to provide SDIDTK facilities and infrastructure at Posyandu.